Tra locale e globale. Sostenibilità ed empowerment nelle retoriche delle esperienze di microcredito - Giovanna Guerzoni; Francesca Crivellaro (EtnoAntropologia, 2014)
Muhammad Yunus (Nobel Peace Prize 2006) success in Bangladesh, has made microcredit a globally widespread practice. Since the early nineties, microcredit has been adopted by international development organizations as the privileged strategy not only in the struggle against poverty, but also in the promotion of women’s empowerment. The paper critically explores the rhetoric  underpinning the discourse on microcredit, sustainability and the impact on local communities of microfinance programs. Special attention is devoted to the case studies concerning the relationship between access to credit by women and empowerment processes.